Role of the railways in the future of air transport - Givoni, M; Banister, D (Routledge, 2007)
The role of the railways in the air transport industry is usually limited to provision of access to airports. However, the development of high-speed rail networks and the congestion and environmental problems faced by the air transport industry suggest the railways could have a greater role in working with the airlines to provide an integrated transport service for medium-distance journeys (up to 800 km). Many air journeys involve two flights and a transfer at a hub airport. The alternative being investigated here would replace air journeys by a rail journey and a flight and a transfer between them at the hub airport. Such integration could offer a positive alternative to aircraft on some routes and lead to railway journeys to airports becoming part of air transport services and not only to provide access to them. Integration could therefore provide a better use of available air capacity rather than duplicating some high-speed rail routes and services.